Patrimonialization and tourism of the petroglyphs of Alto Magdalena, Colombia: two experiences of heritage education - Leal Zabala, José Uriel (2023)
The purpose of this work is to present the systematization of an academic-research experience that from heritage education has been carried out in Girardot as part of a process of patrimonialization of the petroglyphs of Alto Magdalena region from Colombia. Two academic programs at University of Cundinamarca, Bachelor degree in Education in Humanities: Spanish and English and Technology in Tourism and Hotel Management, have carried out research and itinerant pedagogical practices in the areas of the petroglyphs as part of a process of heritage education and research formative. Through an ethnographic look and an approach from the social imaginaries it was intended to verify how much the perceptions changed after the field trips. Finally, there are processes of patrimonialization and tourism derived from this heritage education in order for petroglyphs to be recognized as heritage before government bodies and thus develop an economic activation from cultural tourism.